Acute ischemia of bilateral lower extremities as a presenting feature of disseminated mucormycosis endocarditis: A case report - Niranjan Tachamo; Priya Rajagopalan; Salik Nazir; Saroj Lohani; Brian Le; Nitin Patel (Greater Baltimore Medical Center, 2016)
Disseminated mucormycosis endocarditis is extremely rare, and only a few cases have actually been reported in the literature. It is almost universally fatal despite aggressive surgical and medical management. In this article, we present the case of a 48-year-old immunocompromised male with mucormycosis endocarditis, who presented with acute bilateral lower extremity ischemia and passed away due to subsequent multi-organ failure. To our knowledge, this is the first case report of disseminated mucormycosis native valve endocarditis presenting as acute bilateral lower extremity ischemia.